Recycling of Myths in Contemporary Nepali Art - Rajbhandari, Jasmine (Journal of Fine Arts Campus, 2024)
This article presents the ‘recycling of myth’ in Nepali art. Nepali artists distorted such stories, characters, and emotions in their art to create unity in communication by transforming these stories from past generations to upcoming generations. This writing explores the relationship between myth and the art of Nepali artists, using their works as examples. The artworks are analyzed using qualitative research methods. They sometimes painted those stories precisely according to what was written in the text in their style. In some paintings, they distort the myth to explain their perspective about the world, political situation, and nature. These depictions of myth symbolically teach love, respect, unity, and moral lessons to society. The artists utilizing this have unique styles and are achieving great success. Information acquired by analysis of individual artworks leads to finding the meaning of works.